Deteksi Ketuban Pecah Dini Menggunakan Pantyliner Berbahan Ekstrak Kunyit - Isnaniah, Isnaniah; S.Tr.Keb, Noor Adha Aprilea; Prihatanti, Nur Rohmah; Barkinah, Tut (Jurnal Skala Kesehatan, 2024)
Introduction: Premature rupture of membranes (KPD) refers to the amniotic sac rupture before the onset of labor. It occurs in approximately 10% of pregnancies, with 7% in term and 3% in preterm pregnancies. While KPD itself does not directly cause maternal death, it is a significant precursor to infections that can lead to maternal and fetal mortality. Current diagnostic methods for KPD primarily utilize synthetic litmus paper to detect pH changes. However, natural alternatives such as turmeric, a traditional plant-based pH indicator, offer a promising and cost-effective solution. Turmeric contains coumarin, a compound with litmus-like properties, enabling it to identify KPD by reacting with acidic amniotic fluid. Materials and Method: This experimental study was conducted at Sultan Suriansyah Hospital, Banjarmasin City, between January and July 2024. The participants included pregnant women identified as being at risk of KPD. The study explored the efficacy of pantyliners infused with turmeric extract as a diagnostic tool for KPD detection. Results: The findings revealed a significant correlation (ρ < α 0.05) between the color change in turmeric-infused pantyliners and KPD diagnosis. This demonstrates the potential of turmeric-infused pantyliners as a reliable and efficient detection tool for KPD. Discussion/Suggestions: With a diagnostic accuracy of 90%, turmeric-infused pantyliners present a non-invasive, accessible method for early KPD detection. Further studies are recommended to optimize pantyliner formulations, particularly those containing curcumin, and to conduct extensive clinical trials on larger populations.